2013
DOI: 10.1590/0074-0276108052013003
|View full text |Cite
|
Sign up to set email alerts
|

Influenza A virus infection of healthy piglets in an abattoir in Brazil: animal-human interface and risk for interspecies transmission

Abstract: Asymptomatic influenza virus infections in pigs are frequent and the lack of measures for controlling viral spread facilitates the circulation of different virus strains between pigs. The goal of this study was to demonstrate the circulation of influenza A virus strains among asymptomatic piglets in an abattoir in Brazil and discuss the potential public health impacts. Tracheal samples (n = 330) were collected from asymptomatic animals by a veterinarian that also performed visual lung tissue examinations. No s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…Nonetheless, H1N1pdm09 was observed to have circulated among these pigs during both years of the study. This is also similar to previous results obtained from studies in Nigeria [20,42], Togo, also in West Africa [16], and Brazil [43] during which influenza viruses were detected among apparently healthy pigs. This underscores the importance of strict adherence to measures which reduce interspecies transmission of influenza viruses at the human-swine interface.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Nonetheless, H1N1pdm09 was observed to have circulated among these pigs during both years of the study. This is also similar to previous results obtained from studies in Nigeria [20,42], Togo, also in West Africa [16], and Brazil [43] during which influenza viruses were detected among apparently healthy pigs. This underscores the importance of strict adherence to measures which reduce interspecies transmission of influenza viruses at the human-swine interface.…”
Section: Discussionsupporting
confidence: 92%
“…This is similar to the findings of Amorim et al . who reported that continuous exposure of abattoir workers to pigs in Brazil increased the risk for interspecies transmission of influenza A virus [43]. Second, because of very dismal levels of personal and environmental hygiene observed at the abattoir, viruses shed by abattoir workers during the symptomatic phase of influenza could readily infect these pigs.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is speculated that IAV infectious aerosols originated in pig farms could be transported downwind (167). Similar studies conducted in Brazil have also identified that 9% of asymptomatic piglet tracheal samples showed IAV positivity in RT-PCR (168). Hence, continuous exposure of farm animals or humans to the aerosols generated in-farm could potentiate zoonotic IAV transmission to human caretakers.…”
Section: Transmission Of Influenza Virusesmentioning
confidence: 83%
“…Rajão and co-workers [42] reported 38.3% positive human serum samples in serological survey. Continuous exposure of the abattoir workers to animals suffering from subclinical influenza virus infections provided an environment conducive to the occurrence of interspecies infections and the emergence of new potentially pathogenic viral variants [43]. Pregnant women are at greater risks of acquiring swine flu.…”
Section: Streptococcal Meningitis-the Disease Is Caused Bymentioning
confidence: 99%